(untitled) (Social and Environmental Law Journal, 2023)
Press freedom is the focus of this article, emphasizing the search for social representation of certain subjects in relation to this fundamental principle in times of pandemic. The main objective was to study the thinking of academics, professors and health professionals in relation to the performance of the press during the Covid-19 period, analyzing the thoughts of these individuals regarding the work of the media. The survey had the participation of 150 respondents who answered two evocation questions. The first in which the inducing term was “Freedom of the Press” and the second in which the key expression was “Press and Pandemic. The results were treated in the Iramuteq system, the first question being verified through the frequency table showing the most evoked words. From this perspective, it was shown that representation turned to the existence of freedom, which is a right of democracy in the function of bringing the news to the people. In the second strand, the responses generated a maximum tree, in which the main trunks highlighted the Fake News, information, vaccine and society vernaculars. The idea showed that people think that the media in the pandemic should provide information, take care not to spread falsehoods and focus on social benefits in the dissemination of the vaccine. The final reflection led us to believe that journalism cannot be censored, as we live in a Democratic State of Law, true information must be disclosed in the public interest.